2017
DOI: 10.1038/srep44291
|View full text |Cite
|
Sign up to set email alerts
|

Excretion rates of 1,5-anhydro-D-glucitol, uric acid and microalbuminuria as glycemic control indexes in patients with type 2 diabetes

Abstract: 1,5-anhydroglucitol (1,5-AG), uric acid and urinary proteins are excreted into the urine with increasing glucosuria. In the present retrospective study we analyzed whether these factors could be used as indicators for type 2 diabetes mellitus (T2DM) glucose control in 6,766 (T2DM) patients. There were 3,988 cases (58.9%) with HbA1c ≤ 6.5%, 853 cases (12.61%) with HbA1c levels ranging from 6.5% to 7% and 1,925 cases (28.5%) with HbA1c > 7%. HbA1c percentages were correlated with age, MA and 1,5-AG serum concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…1) showed that the addition of liraglutide improved glycemic control compared with CSII alone, manifested by decreased FBG and estimated HbA1c. As previous studies have shown, 1,5-AG is a new clinical marker for glycemic control in patients with type 2 diabetes [23,24]. In this study, we found that the serum 1,5-AG concentration in the CSII combined with liraglutide group was significantly higher than that in the CSII alone group (Table 2), which may further imply that glycemic control with CSII combined with liraglutide is better than with CSII.…”
Section: Discussionsupporting
confidence: 63%
“…1) showed that the addition of liraglutide improved glycemic control compared with CSII alone, manifested by decreased FBG and estimated HbA1c. As previous studies have shown, 1,5-AG is a new clinical marker for glycemic control in patients with type 2 diabetes [23,24]. In this study, we found that the serum 1,5-AG concentration in the CSII combined with liraglutide group was significantly higher than that in the CSII alone group (Table 2), which may further imply that glycemic control with CSII combined with liraglutide is better than with CSII.…”
Section: Discussionsupporting
confidence: 63%
“…No differences in 1,5-AG levels were found in patients with markedly different estimated glomerular filtration rates [18], and these levels were not influenced by administration of a gliptin compound [19]. Serum 1,5-AG concentration is a marker for hyperglycemia and may be particularly useful as an indicator for short-term glycemic excursions [20] and is significantly higher in DM patients [21]. Finally, 1,5-AG might suppress the blood glucose elevation through inhibition of sucrase and intestinal glucose absorption [22].…”
Section: Discussionmentioning
confidence: 99%
“…There are reports showing that controlling blood glucose in the nonfasting state, especially in the postprandial period can reduce the risk of diabetic complications. 10,11 Given the presence of dysglycemic individuals who are only postprandial hyperglycemia, serum 1,5-AG may be a useful marker of diabetes. 7 Recent evidence shows that plasma concentrations of 1,5-AG show decreases at the highest levels of blood glucose and reflect glucose excursions.…”
Section: Discussionmentioning
confidence: 99%
“…10 These observations support the usefulness of 1,5-AG as a marker of short-term glycemic variability for the assessment and preventing of GDM complications. 11 The strength of our study is the inclusion of 1 h glucose values. In some previous studies using different diagnostic criteria 1 h glucose values were not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation